Bearing Tribology Principles and Applications - Qiu, Ming; Chen, Long; Li, Yingchun; Yan, Jiafei (Springer Berlin Heidelberg : Imprint: Springer, 2017)
By focusing on the theory and techniques of tribological design and testing for bearings, this book systematically reviews the latest advances in applications for this field. It describes advanced tribological design, theory and methods, and provides practical technical references for investments in bearing design and manufacturing. The theories, methods and cases in this book are largely derived from the practical engineering experience gained and research conducted by the author and her team since the 2000s. The book includes academic papers, technical reports and patent literature, and offers a valuable guide for engineers involved in bearing design. <The book is intended for engineers, researchers and graduate students in the field of mechanical engineering, especially in bearing engineering.